Framed? Judicialization and the Risk of Negative Episodic Media Coverage. Issue 3 (2nd January 2018) - Barnes, Jeb; Hevron, Parker
Abstract : Activists on the left and right have increasingly turned to the courts to make policy, raising questions about the potential risks of judicialization. One possibility is that litigation is more prone to negative episodic media coverage than alternative modes of policymaking. Using across‐ and within‐policy area comparisons of stories about the Federal Black Lung Program, collective asbestos litigation strategies, and individual asbestos tort suits, we find that coverage becomes steadily more episodic and critical as it focuses on policy regimes that feature increasing amounts of adversarial legalism. Moreover, even the broadest coverage of asbestos litigation fails to explain why victims of asbestos turned to the courts, how powerful interests constrained their policy options, or how judges urged Congress to act. This limited and relatively critical anecdotal reporting implies that litigation may engender less favorable media coverage than its alternatives and that activists should weigh this risk when deciding to litigate.